Comprehensive analysis of H3K27me3 LOCKs under different DNA methylation contexts reveal epigenetic redistribution in tumorigenesis - Yuan Liang; Mengni Liu; Bingyuan Liu; Benjamin Ziman; Guanjie Peng; Qiong Mao; Xingzhe Wang; Lizhen Jiang; De-Chen Lin; Yueyuan Zheng (Epigenetics & Chromatin)
Abstract Background Histone modification H3K27me3 plays a critical role in normal development and is associated with various diseases, including cancer. This modification forms large chromatin domains, known as Large Organized Chromatin Lysine Domains (LOCKs), which span several hundred kilobases. Result In this study, we identify and categorize H3K27me3 LOCKs in 109 normal human samples, distinguishing between long and short LOCKs. Our findings reveal that long LOCKs are predominantly associated with developmental processes, while short LOCKs are enriched in poised promoters and are most associated with low gene expression. Further analysis of LOCKs in different DNA methylation contexts shows that long LOCKs are primarily located in partially methylated domains (PMDs), particularly in short-PMDs, where they are most likely responsible for the low expressions of oncogenes. We observe that in cancer cell lines, including those from esophageal and breast cancer, long LOCKs shift from short-PMDs to intermediate-PMDs and long-PMDs. Notably, a significant subset of tumor-associated long LOCKs in intermediate- and long-PMDs exhibit reduced H3K9me3 levels, suggesting that H3K27me3 compensates for the loss of H3K9me3 in tumors. Additionally, we find that genes upregulated in tumors following the loss of short LOCKs are typically poised promoter genes in normal cells, and their transcription is regulated by the ETS1 transcription factor. Conclusion These results provide new insights into the role of H3K27me3 LOCKs in cancer and underscore their potential impact on epigenetic regulation and disease mechanisms.